2007
DOI: 10.1177/002214650704800205
|View full text |Cite
|
Sign up to set email alerts
|

The Life-Course Origins of Mastery among Older People

Abstract: In this article, we aim to identify the sources of mastery--the understanding that individuals hold about their ability to control the circumstances of their lives. The sample for our inquiry was drawn from the Medicare beneficiary files of people 65 and older living in Washington, DC, and two adjoining Maryland counties. We find that past circumstances, particularly those reflecting status attainment and early exposure to intractable hardships, converge with stressors experienced in late life to influence eld… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
140
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(153 citation statements)
references
References 28 publications
13
140
0
Order By: Relevance
“…Feeling that one is doing well in comparison to one's peers will be associated with self-ef fi cacy which, in turn, is bene fi cial to one's functioning. This act of re fl ecting and evaluating one's life as favorable is similar to the development of mastery in later life (Pearlin, Nguyen, Schieman, & Milkie, 2007 ) . The point is that people have a sense of how they are doing in life, whether they have overcome or succumbed to adversity, and these evaluations of their life trajectory in fl uence their view of the future and sense of hope (Schafer, Ferraro, & Mustillo, 2011 ) .…”
Section: Cumulative Inequality Theorymentioning
confidence: 95%
“…Feeling that one is doing well in comparison to one's peers will be associated with self-ef fi cacy which, in turn, is bene fi cial to one's functioning. This act of re fl ecting and evaluating one's life as favorable is similar to the development of mastery in later life (Pearlin, Nguyen, Schieman, & Milkie, 2007 ) . The point is that people have a sense of how they are doing in life, whether they have overcome or succumbed to adversity, and these evaluations of their life trajectory in fl uence their view of the future and sense of hope (Schafer, Ferraro, & Mustillo, 2011 ) .…”
Section: Cumulative Inequality Theorymentioning
confidence: 95%
“…Regardless of the source of advantage, the advantaged have large initial gains that accumulate over the lifetime, resulting in positive outcomes (Elder 1998;O'Rand and Hamil-Luker 2005;Pearlin et al 2007;Shuey and Willson 2008). The converse is also true: those who are disadvantaged become increasingly disadvantaged.…”
Section: Cumulative Inequality/disadvantage Modelsmentioning
confidence: 99%
“…For example, Schieman and Turner (1998) found that higher age and disability were related to lower levels of mastery; and higher education levels were believed to predict greater personal control (Hitlin & Long, 2009). Moreover, Pearlin, Nguyen, Schieman, and Milkie (2007) noticed that extended education would indirectly influence the lifecourse mastery of older people 'through the greater occupational and financial opportunities' provided by education after high school (p. 173). Other authors indicated that although mastery is responsive to circumstances, it can also operate as a capacity (Skaff et al, 1996): it might buffer the impact of decrease in physical health on older people's well-being (Jonker, Comijs, Knipscheer, & Deeg, 2009), and it could buffer against the anxiety related to disability problems (Krokavcova et al, 2008).…”
Section: Literature Overviewmentioning
confidence: 99%